Treatment of Chronic Haemophilic Synovitis with PRP: Clinical and In Vitro Studies - Caviglia, Horacio Alberto (2024)
Intra-articular blood, iron and hemosiderin, hydroxyl radical cytokines, and neo-angiogenesiscause synovial inflammation, which leads to cartilage and joint damage. Platelet-rich plasma (PRP)inhibits most of the mediators that produce and maintain synovitis. We compile here our workshowing the clinical effectiveness of intra-articular PRP injections and their potential role in stoppingarticular cartilage damage due to bleeding and its possible repair. A total of 116 joints, includingknees (63%), elbows (19.8%), and ankles (17.2%), were treated with intra-articular injections of PRP.Moreover, we also show here the number of extracellular DNA traps (ETs) and the PRP effect in thesynovial fluid of patients at the time of treatment and six months after. Clinically, it is demonstratedthat PRP is effective in reducing bleeding episodes (p < 0.001) and pain (p < 0.0001) and improvingthe hemophilia joint health score (HJHS) (p < 0.001) at one year of follow-up. Furthermore, our resultsdemonstrate that PRP inhibits ET formation in vitro and reconstitutes the immune system’s cellularcomponents in the synovial fluid of patients after treatment. We conclude that PRP can be consideredan effective, safe, and easy treatment for hemophilic synovitis.